Landscape modeling through remote sensing data for central and western Bahia, Brazil - Oliveira, Luciel Passos de; Cruz, Uilmer Rodrigues Xavier da (Revista Cerrados, 2025)
This study presents a discussion on the spatial modeling of landscapes through remote sensing techniques, initially presenting a conceptual discussion on the topics related of modeling, remote sensing, and landscapes. The study offers the following research question: How to represent the diversity of landscapes with their environmental components that are sensitive to anthropic actions in central and western Bahia? Given this issue, the research the general purpose of: representing the points with the highest environmental vulnerability. The study area of this research corresponds to the areas located in the central portion, alongside the western territory of the state of Bahia, Brazil. Through procedures encompassing remote sensing and digital image processing, it was possible to achieve the result to generate and quantify a representative model for the aspects of land cover which enabled analysis and subsequent recommendations for environmental issues inherent to the reality of the investigated area.